STRATEGI PEMBELAJARAN KOOPERATIF DALAM MENINGKATKAN MOTIVASI BELAJAR - Kusen Kusen (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2016)
Abstract Learning is an interactive process between students and teacher. In order to motivate students to learn, cooperative leaning is really needed. The cooperative leaning gives big advantages to make students more active in the classroom. Students are possible to change ideas. As a result, their motivation are enhanced, their creativity are improved, and their potential were increased. In addition to this, students are not bored in learning. Due to good advanteges of cooperative leaning, it is recommended to use this technique in the classroomKata Kunci: Pembelajaran, kooperatif, dan motivasi.